2021
DOI: 10.1021/acsomega.1c05817
|View full text |Cite
|
Sign up to set email alerts
|

Novel Short Process for p-Xylene Production Based on the Selectivity Intensification of Toluene Methylation with Methanol

Abstract: Toluene methylation using methanol offers a high potential molecular engineering process to produce p -xylene (PX) based on shape-selective catalysts. To further improve the process economics, a novel short process was proposed by reducing the high-energy consumption separation of xylene isomers in existing processes since the PX selectivity of the xylene isomers can be enhanced more than the industrial product quality of 99.7%. The PX selectivity intensification was achieved as a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…To demonstrate the versatility of cross-linked brush membranes, we tested two commercially relevant feed solutions: (i) 80–20 mol % methanol–toluene and (ii) 95–5 mol % toluene–triisopropyl benzene (TIPB). The methanol–toluene mixture is an industrially important separation frequently encountered in the synthesis of pharmaceuticals and fine chemicals. , The molecular weights of methanol and toluene are 32 and 92 g/mol, respectively, and mixtures form a low boiling azeotrope at high methanol concentrations. Additionally, this mixture is commonly separated by energy-intensive distillation or low-throughput adsorption and therefore presents an opportunity to use synthetic membranes to increase capacity and reduce cost.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the versatility of cross-linked brush membranes, we tested two commercially relevant feed solutions: (i) 80–20 mol % methanol–toluene and (ii) 95–5 mol % toluene–triisopropyl benzene (TIPB). The methanol–toluene mixture is an industrially important separation frequently encountered in the synthesis of pharmaceuticals and fine chemicals. , The molecular weights of methanol and toluene are 32 and 92 g/mol, respectively, and mixtures form a low boiling azeotrope at high methanol concentrations. Additionally, this mixture is commonly separated by energy-intensive distillation or low-throughput adsorption and therefore presents an opportunity to use synthetic membranes to increase capacity and reduce cost.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15 , 16 ] Another major feature is the availability of pure p- xylene from the other isomers. As demonstrated by Wang et al [ 17 ], the production of p- xylene is still a challenge. Most catalytic systems tend to perform poorly when applied to the other isomers, and there is also a need to address the difficulty of separation.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Generally, PX is produced using CO 2 as C1 feedstocks through two routes. One is the indirect methylation route including CO 2 hydrogenation to methanol 11,12 and subsequent methanol methylation with toluene, 7,13,14 where the metal oxide (MO X ) and modified zeolite are the catalysts for these two steps separately. The other one is the direct methylation route upon a bifunctional catalyst combining CO 2 hydrogenation and methylation as a tandem catalysis process.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, PX is produced using CO 2 as C1 feedstocks through two routes. One is the indirect methylation route including CO 2 hydrogenation to methanol , and subsequent methanol methylation with toluene, ,, where the metal oxide (MO X ) and modified zeolite are the catalysts for these two steps separately. The other one is the direct methylation route upon a bifunctional catalyst combining CO 2 hydrogenation and methylation as a tandem catalysis process. Similarly, syngas (CO + H 2 ), as another C1 feedstock, has also been introduced in the direct methylation route, while direct CO 2 methylation with benzene has also demonstrated to be more advantageous. , For direct CO 2 methylation, Zuo and Yuan et al concluded that the methoxy H 3 CO* species formed on MO X preferably migrate into the channel of zeolite for methylation with adsorbed toluene rather than desorb as methanol.…”
Section: Introductionmentioning
confidence: 99%